Penanganan Longsoran Jalan Nasional Padangsidimpuan – Batas Sumatera Barat Dengan Dinding Penahan Tanah Tipe Kantilever: National Road Slide Management Padangsidimpuan – West Sumatra Border With Cantilever Type Soil Retaining Wall - Muda, Anwar (Media Ilmiah Teknik Sipil, 2022)
50 dan aman terhadap daya dukung, karena FS daya dukung = 4,16 ≥ FS = 3,00. Kata kunci : Penanganan, Longsoran, Dinding penahan, Kantilever ABSTRACT The background of the research is that the national road sta 20+550, section 039 or to be precise in Silaiya Village, Sayurmatinggi District, South Tapanuli Regency, North Sumatra, an avalanche occurred about 3 years ago. Then, the location of this avalanche has never been handled either by masonry or cantilevered buildings or other structures. For this reason, landslide management is carried out with a cantilever type retaining wall 22 meters long, 2.60 meters deep from the asphalt surface and a base plate width of 2.00 meters. Then, the top wall thickness is 0.40 meters and the bottom is 0.50 meters. The result of the calculation is that the cantilever type retaining wall for national road sta 20+550 section 039 is safe against overturning, because FS bolsters = 8.72 ≥ FS = 2.00. Then, this retaining wall is safe against shear, because FS shear = 1.53 ≥ FS = 1.50 and safe against bearing capacity, because FS bearing capacity = 4.16 ≥ FS = 3.00